(untitled) (Sahel Journal of Life Sciences FUDMA, 2025)
This study, conducted in Katsina, Nigeria, investigated antibiotic resistance in Staphylococcus aureus and Escherichia coli from patients with Diabetic Foot Infections (DFIs). 150 wound samples were collected, identifying 44 isolates (22 S. aureus and 22 E. coli). Results showed high resistance rates: E. coli was 100% resistant to cefuroxime, ciprofloxacin, ofloxacin, augmentin, ampicillin, and erythromycin. S. aureus showed 100% resistance to pefloxacin, 95% to ciprofloxacin, and 45% to cefoxitin. All E. coli and six S. aureus isolates were multidrug-resistant (MDR). PCR confirmed resistance genes: blaTEM and blaCTX in E. coli, and mecA and parC in S. aureus. The study highlights MDR pathogens in DFIs, emphasizing the need for surveillance and improved antimicrobial stewardship in Katsina State. DFIs are a significant concern, and antibiotic resistance is a major challenge. Effective treatment strategies and infection control measures are crucial to prevent further resistance.